Innate and adaptive immune response in SARS-CoV-2 infection-Current perspectives - Zhu, Qiugang; Xu, Yan; Wang, Ting; Xie, Feiting (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), a novel coronavirus strain with strong infectivity that has caused a global pandemic. With the in-depth research, the close relationship between COVID-19 and immune system has been dug out. During the infection, macrophages, dendritic cells, natural killer cells, CD8+ T cells, Th1, Th17, Tfh cells and effector B cells are all involved into the anti-SARS-CoV-2 responses, however, the uncontrolled immune responses can result in the excessive inflammation, acute lung injury, and even other organ failure. Thus, a comprehensive understanding of immune response during COVID-19 will provide insights in predicting disease outcomes and developing appropriate therapies. In this reviews, we mainly clarify the immune responses elicited by SARS-CoV-2 and aim to propose new insights into target-vaccine development and treatment.